Association between triglyceride-glucose and triglyceride-glucose related indices with all-cause mortality in depression participants: a cohort study from NHANES - Wang, Xinxing; Feng, Chengya; Zhang, Bo; Jiang, Guosong (Frontiers in Psychiatry, 2025)
BackgroundWhile the triglyceride-glucose (TyG) index and related indices have been recognized as markers of insulin resistance and cardiometabolic disorders, few studies have examined their association with all-cause mortality in individuals with depression. This study aimed to investigate the relationship between the TyG index, its related indices, and all-cause mortality among patients with depression in the United States.MethodsA total of 3,179 patients with depression were identified from the National Health and Nutrition Examination Survey (NHANES, 2005–2018). Participants were categorized into tertiles (T1, T2, T3) based on the TyG index and its derived indices: TyG combined with body mass index (TyG-BMI), waist circumference (TyG-WC), and waist-to-height ratio (TyG-WHtR). Cox regression analysis and Kaplan–Meier curve analysis were used to explore the relationship between the independent variable TyG and its derived indicators and the dependent variable all-cause mortality.Curve fitting and threshold effect analyses were performed to evaluate potential nonlinear or dose-response relationships. Subgroup and sensitivity analyses were conducted to validate the robustness of the results.ResultsOver a 13-year follow-up period, both the lowest and highest tertiles of the TyG index and its related indices were associated with significantly increased risks of all-cause mortality compared to the middle tertile. Restricted cubic spline analysis revealed U-shaped nonlinear relationships between these indices and all-cause mortality, with distinct threshold effects. Among the indices, TyG-BMI and TyG-WC demonstrated the strongest associations, though similar trends were observed for the other TyG-related indices.ConclusionThis study identified nonlinear associations between the TyG index and its related indices (TyG-BMI, TyG-WC, TyG-WHtR) and all-cause mortality in patients with depression, with clear threshold effects. These findings highlight the potential utility of stratified risk assessment and targeted interventions based on these thresholds.